Dança do Congo : educação, expressão, identidade e territorialidade - Oliveira, Herman Hudson de (2011)
In the city Nossa Senhora do Livramento, also known as Livramento, located on highway MT-060, towards the Pantanal of Mato Grosso and which is about 40 km from the state capital, Cuiabá, there is the Dance of the Congo, artistic expression characteristic of rural black communities. This “ritual-theater” represents the war between two kingdoms (probably Congo and Angola) and has the center of the matter, the dispute of a territorial issue. The base of this artiste’s expression that combines scenery, choreography, drama and music, is the devotion to St. Benedict and happens in the months of April and July, respectively in Livramento and Mutuca. It rises in Mutuca within the complex which is Sesmaria Boa Vida, which is a slave descendant’s community (quilombo), divided, therefore, into six associations. The ethnographic and historical bases were investigated in an attempt to understand whether the musicality of the Congo is related with environmental and how this knowledge approaches to an inventive pedagogy. Either their dancers and the story they tell, the Dance of the Congo also undergoes into an identity and diaspora’s process since it extent to the environmental pedagogies while the territorial notions play in reframing and updating historical and ethnographic senses belonging to the Quilombo. However components of socioeconomic and socio-environment interact and interfere with the temporal and spatial dynamics of this web of meanings and relationships by taking as the main element of power relations. Synergistically to modern rationality, capitalism presses the communities and their expressions for “between places” of culture and meaning of the subjects in relation to their places of origin, requiring other ways of thinking about themselves and their art. However an iconographic element, St. Benedict, installs itself as central role of elements of identity, territories and artistic; precisely at the point where the black communities to reinvent themselves in religiosity.